A framework for QoS-aware software components. - Menascé, Daniel A.
The next generation of software systems will be highly distributed, component-based, service-oriented, will need to operate in unattended mode and possibly in hostile environments, will be composed of a large number of "replaceable" components discoverable at run-time, and will have to run on a multitude of unknown and heterogeneous hardware and network platforms. This paper focuses on service oriented-architectures in which each component provides a set of interrelated services to other components. These components are QoS-aware (i.e., aware of Quality of Service requirements) and are capable of engaging in QoS negotiations with other components of a distributed application. The main contributions of this paper are: i) the description of an architecture for QoS-aware software components that are able to negotiate QoS requirements with other components, ii) the specification of the protocols used for QoS negotiation and admission control at the QoS-aware components, iii) a report on the implementation of a QoS-aware component, and iv) the experimental validation of the ideas presented in the paper.
Keywords: Information systems; Information systems applications; Software; Software engineering; Metrics; Performance measures; Complexity measures